Study on Borehole Arrangement Methods for Gas Extraction by Hydraulic Slotting in Long-Distance Through-Coal Seam Tunnel. (28th October 2020) - Zhu, Cunfang; Cai, Shuang
Abstract : How to quickly eliminate outburst in long-distance through-coal seam tunnels is one of the major challenges faced by the tunnel industry in mountainous areas. Compared with coal mine rock crosscut coal uncovering, the work surrounding the rock of through-coal seam tunnels has a high degree of breakage, large cross-section of coal uncovering, and tight time and space. In this paper, a method of networked slotting in long-distance through-coal seam tunnels for rapid pressure relief and outburst elimination is proposed. Based on this method, the corresponding mathematical governing equations and numerical simulation models have been established. The optimal borehole arrangement spacing and the slot arrangement spacing obtained by numerical optimization are 2.85 m and 3.1 m, respectively. Field gas production data of through-coal seam tunnels show that compared with the traditional dense-borehole gas extraction, the method of networked slotting in long-distance through-coal seam tunnels for rapid pressure relief and outburst elimination can shorten the extraction time by about 66%, the net quantity of peak extraction is increased by 3.55 times, and the total quantity of gas extraction when reaching the outburst prevention index is increased by 1.26 times, which verifies the feasibility of this method and the reliability of numerical simulation results. This study could be used as a valuable example for other coal deposits being mined under similar geological conditions.